Registered report: Discovery and preclinical validation of drug indications using compendia of public gene expression data - Kandela, Irawati; Zervantonakis, Ioannis; Reproducibility Project: Cancer Biology (eLife, 2015)
The Reproducibility Project: Cancer Biology seeks to address growing concerns about reproducibility in scientific research by conducting replications of 50 papers in the field of cancer biology published between 2010 and 2012. This Registered report describes the proposed replication plan of key experiments from ‘Discovery and Preclinical Validation of Drug Indications Using Compendia of Public Gene Expression Data’ by Sirota et al., published in Science Translational Medicine in 2011 (Sirota et al., 2011). The key experiments being replicated include Figure 4C and D and Supplemental Figure 1. In these figures, Sirota and colleagues. tested a proof of concept experiment validating their prediction that cimetidine, a histamine-2 (H2) receptor agonist commonly used to treat peptic ulcers (Kubecova et al., 2011), would be effective against lung adenocarcinoma (Figure 4C and D). As a control they also tested the effects of cimetidine against renal carcinoma, for which it was not predicted to be efficacious (Supplemental Figure 1). The Reproducibility Project: Cancer Biology is a collaboration between the Center for Open Science and Science Exchange, and the results of the replications will be published by eLife.
Keywords: methodology; Reproducibility Project: Cancer Biology; drug retargeting